The Factors That Influencing Employee Job Satisfaction: Case of Selected SME in Klang Valley - Krishnan, Thanigaivel R. (2012)
The object of this study was to examine the factors affecting employee job satisfaction at Small and Medium Enterprise (SME) amongst employees. In this research the population targeted employees of SME. The study was conducted at selected SME in Klang Valley. The data was collected and administered by means of a structured questionnaire based on the Minnesota job satisfaction questionnaire (MSQ). The study showed that factors such as work conditions, pay, fairness, and promotion significantly influenced employee job satisfaction in SMEs. However, factors such as age and gender did not significantly influence employee job satisfaction in SMEs. The study provided a good understanding regarding the factors affecting job satisfaction in SMEs. Therefore, it emphasizes that there is still a need to conduct extra research to filling the gaps that have not been solved in the current study. In the Chapter 5, few recommendations were provided for future use to any researcher in this academic field.